PENINGKATAN PROFESIONALISME PEGAWAI NEGERI SIPIL DILIHAT DARI SISTEM REKRUTMEN BERBASIS KOMPETENSI - Ridwan, Muhammad (Nakhoda: Jurnal Ilmu Pemerintahan, 2011)
Quality of human resources-civil servants, among others, which is determined by the recruitment processof seeking and finding HR activities-civil servant who has the motivation, ability, skills and knowledgerequired to carry out its duties in office. Organizational recruitment as human resource planning must becomprehensive programmed to be able to predict the needs of both quantity and quality as well asplanning professionals. Theoretically, many methods and selection techniques to evaluate applicantsaccording to a vacant position within the organizationKeywords: professionalism, recruitment, competence